Diversity and biogeography of Mediterranean freshwater blennies (Blenniidae, Salaria). Issue 9 (16th July 2021) - Wagner, Maximilian; Zogaris, Stamatis; Berrebi, Patrick; Freyhof, Jörg; Koblmüller, Stephan; Magnan, Pierre; Laporte, Martin
Abstract: Aim: In the Mediterranean biodiversity hotspot, freshwater fishes are key biogeographic indicators, while their habitats are vulnerable to ongoing anthropogenic pressures. The freshwater blenny is a widespread endemic taxon in this area. However, our understanding of the overall diversity of specific populations and their phylogenetic relationships is sparse. Thus, we aim to investigate the genetic diversity, infer relationships among sampled populations related to major palaeoenvironmental changes and suggest insights for future research and conservation targets. Location: Mediterranean Basin Methods: We studied 171 Salaria specimens from 51 rivers and lakes, and from 13 countries surrounding the Mediterranean Sea. For assessing the phylogenetic relationships among different locations, we used mtDNA d‐loop and intron S7 sequences. Furthermore, we inferred absolute divergence times and demographic changes using secondary calibrations and investigated the diversity within major lineages using haplotype networks and several geographical and genetic clustering methods. Results: We found eight well‐differentiated lineages, each of which being confined to a particular geographical region. The onset of the freshwater blenny radiation was dated around the Messinian salinity crisis. Further differentiation happened during the Plio‐ and Pleistocene with signatures of population expansion after the Last Glacial Maximum in some of the main lineages. Main conclusions: Due to their unusually widespread distribution, the freshwater blennies represent an excellent model for studying phylogeographic structure across the Mediterranean basin biodiversity hotspot. The extant diversity and distribution of the freshwater Salaria species mirrors palaeoenvironmental changes in the region, but there are still large gaps in knowledge, particularly in the Levant. Even though the main lineages described are statistically well supported, the phylogenetic relationship among several of them remains poorly resolved. Despite the fact that the most widespread species, S. fluviatilis, is not globally threatened, it harbours some distinct populations that are of conservation concern.